2017
DOI: 10.4012/dmj.2016-266
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of strontium in human teeth treated with surface pre-reacted glass-ionomer filler eluate by using extended X-ray absorption fine structure analysis

Abstract: The bioactive effects of strontium released from surface pre-reacted glass-ionomer (S-PRG) fillers may aid in caries prevention. In this study, the local structure of strontium taken up by teeth was estimated by extended X-ray absorption fine structure analysis. Immersing teeth into S-PRG filler eluate increased the strontium content in enamel and dentin by more than 100 times. The local structure of strontium in enamel and dentin stored in distilled water was the same as that in synthetic strontium-containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…In recent years, many studies of bioactive materials have been conducted [34,35,36]. The results of this study may be useful to the development of biomaterials.…”
Section: Discussionmentioning
confidence: 88%
“…In recent years, many studies of bioactive materials have been conducted [34,35,36]. The results of this study may be useful to the development of biomaterials.…”
Section: Discussionmentioning
confidence: 88%
“…Similar results have also been reported for other S-PRG fillercontaining materials such as orthodontic adhesives 83) , fissure sealants 84) , coating materials 54,85) , resinous vanishes 86) and denture base resins 87) . Uo et al 88) investigated the local structure of strontium taken up by teeth using X-ray absorption fine structure analysis, and revealed that the strontium content in enamel and dentin was 100 times greater after immersion in the eluate of S-PRG filler than before immersion. It is known that strontium enhances the acid resistance of teeth by converting hydroxyapatite to strontiumapatite 89,90) .…”
Section: Ion-releasing Glass Fillersmentioning
confidence: 99%
“…Sr K-edge XAFS spectra were measured on NW-10A beamlines at the Photon Factory of the High Energy Accelerator Research Organization (Tsukuba, Japan) by using the transmission method. Measurement and EXAFS analysis were described in the previous report 19) . Table 2 shows the time dependence of B, Na, Mg, Al, Zn, and Sr content in natural enamel and in enamels immersed in S-PRG eluate for various periods, up to 28 days; these time-dependence data are also plotted in however, it was also present in the enamel in high concentrations (7,000 ppm in approx.…”
Section: Quantitative Analyses Of Element Concentrations In Enamel Pomentioning
confidence: 99%
“…In both cases, Sr and F penetration into dentin and enamel from the interface with the S-PRGcontaining material occurred for an extended period. Notably, Sr was reported to accumulate in the enamel and dentin for 3 months with S-PRG eluate immersion; this accumulated Sr was speculated to incorporated to the Ca site of HAP 19) . By using PIXE, Nakamura et al revealed Sr enrichment on the enamel surface after 40 min of contact with an S-PRG-containing experimental toothpaste 14) ; their report suggested that early Sr incorporation could occur in less than 1 h, and that the acid resistance of enamel was improved.…”
Section: Introductionmentioning
confidence: 99%